Análisis de los cambios en la cobertura de bosque en el municipio de San Vicente del Caguán, Caquetá, en el período 2021-2023 (2025)
Deforestation is a process in which there is transformation and loss of forest areas, mainly due to human activities such as agriculture, livestock and urban growth. From the above, it can be understood that deforestation is a phenomenon that involves the change of land cover of cover categories relatively natural areas such as forests or forest areas to other types of higher coverage anthropic agency, that is: those stimulated by intensive human activity. This Change in land cover not only reduces the extent of forests, but also It also alters ecosystems, affects biodiversity and contributes to climate change by release large amounts of carbon stored in vegetation and soil (Global Forest Watch, 2024).